A study to investigate knowledge levels on the appropriate use of metered dose inhaler by community pharmacist in lusaka - Chanda, Nkatya Melvin (Lusaka: University of Zambia , School of Medicine, 2016)
Metered dose inhalers (MDI) are commonly used by asthma and chronic obstructive pulmonary disease (COPD) patients. Incorrect MDI technique by patients leads to poor outcome of the outcome of the treatment. Insufficient skill in the use of MDI device by pharmacists worldwide was reported. The aim of this study was to assess the community pharmacists's competency on MDI technique use in Lusaka and to identify the factors affecting the competency on MDI technique use among the community pharmacists in Lusaka.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Pharmacy.
Includes bibliographical references.
Keywords: Metered-dose inhalers; Toluene diisocyanate; Metered-dose inhalers - usage